Outcomes of random start versus clomiphene citrate and gonadotropin cycles in occult premature ovarian insufficiency patients, refusing oocyte donation: a retrospective cohort study - Hatirnaz, Safak; Basbug, Alper; Akarsu, Suleyman; Hatirnaz, Ebru; Demirci, Hakan; Dahan, Michael H (Gynecological endocrinology, 2018)
The aim of this study is to present the clinical outcomes of a random start, a spontaneous folliculogenesis protocol versus Clomiphene Citrate and Gonadotropin treatment in women with occult premature ovarian insufficiency. Women underwent treatment between 1 February 2009, and 30 May 2016. 41 women were treated with the random start protocol while 48 cases received ovarian stimulation with clomiphene and gonadotropins. All included cases met the criteria of 4 months of oligo-ovulation, follicular-stimulating hormone levels over 30 IU/L and anti-Mullerian hormone levels below 0.30 ng/mL. The random start protocol involved following the subjects for up to 6 months until spontaneous folliculogenesis occurred. The mean number of oocytes collected, mature oocytes, fertilized oocytes, and grade II embryos were significantly higher in the random start protocol (p < .05). The doses of gonadotropin administration and hCG were significantly lower in the random start protocol (p < .05). The clinical pregnancy and live birth rates were significantly higher in the random start protocol (p < .05). Likely stimulation is of little benefit in women with occult premature ovarian insufficiency. Observation while waiting for spontaneous folliculogenesis results in better outcomes, and less oocyte collections. 本研究的目的是表明卵泡随机自发发育与克罗米芬柠檬酸和促性腺激素治疗对隐匿性卵巢早衰的妇女产生的不同临床结果。入组女性在2009年2月1日至2016年5月30日期间接受了治疗。41名女性接受随机起始方案, 48例接受克罗米芬和促性腺激素的卵巢刺激。所有病例均符合4个月低排卵、30 IU/L以上促卵泡激素和0.30 ng/mL以下抗苗勒激素水平的诊断标准。随机方案包括跟踪受试者长达6个月, 直到发生自发性卵泡发育。随机起始方案采集的卵母细胞、成熟卵母细胞、受精卵和II级胚胎的平均数量显著高于对照组(p<0.05)。在随机启动方案中, 促性腺激素和hCG的剂量明显降低(p < 0.05)。随机起始方案的临床妊娠和活产率显著高于对照组(p<.05)。对隐匿性卵巢早衰的妇女可能产生的刺激较少。在等待自发卵泡发生的过程中观察, 结果更好, 卵母细胞的数量更少。